Vie chirurgiche d’accesso al gomito in traumatologia - Santolini, F.; Santolini, E.; Mangano, D.; Briano, S.; Sanguineti, F.; Felli, L.; Stella, M. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACHES TO THE ELBOW IN TRAUMA The elbow is a complex anatomical structure. The increasing amount of high energy trauma-related injuries has required the development of several surgical approaches to allow for restoration of the anatomical joint surface and to obtain good clinical outcomes. In this article, we describe the main surgical approaches needed for the treatment of such a complex pattern of traumatic lesions.